Dynamical friction and the evolution of black holes in cosmological simulations: A new implementation in OpenGadget3 - Damiano, Alice (2024)
Aims. We introduce a novel sub-resolution prescription to correct for the unresolved dynamical friction (DF) onto black holes (BHs) in cosmological simulations, to describe BH dynamics accurately, and to overcome spurious motions induced by numerical effects. Methods. We implemented a sub-resolution prescription for the unresolved DF onto BHs in the OpenGadget3 code. We carried out cosmological simulations of a volume of (16 comoving Mpc)3 and zoomed-in simulations of a galaxy group and of a galaxy cluster. We assessed the advantages of our new technique in comparison to commonly adopted methods for hampering spurious BH displacements, namely repositioning onto a local minimum of the gravitational potential and ad hoc boosting of the BH particle dynamical mass. We inspected variations in BH demography in terms of offset from the centres of the host sub-halos, the wandering population of BHs, BH–BH merger rates, and the occupation fraction of sub-halos. We also analysed the impact of the different prescriptions on individual BH interaction events in detail. Results. The newly introduced DF correction enhances the centring of BHs on host halos, the effects of which are at least comparable with those of alternative techniques. Also, the correction becomes gradually more effective as the redshift decreases. Simulations with this correction predict half as many merger events with respect to the repositioning prescription, with the advantage of being less prone to leaving substructures without any central BH. Simulations featuring our DF prescription produce a smaller (by up to ~50% with respect to repositioning) population of wandering BHs and final BH masses that are in good agreement with observations. Regarding individual BH–BH interactions, our DF model captures the gradual inspiraling of orbits before the merger occurs. By contrast, the repositioning scheme, in its most classical renditions, describes extremely fast mergers, while the dynamical mass misrepresents the dynamics of the black holes, introducing numerical scattering between the orbiting BHs. Conclusions. The novel DF correction improves the accuracy if tracking BHs within their hosts galaxies and the pathway to BH- BH mergers. This opens up new possibilities for better modeling the evolution of BH populations in cosmological simulations across different times and different environments.